Viscosity of R134a, R32, and R125 at saturation - Oliveira, Carla Padrel de (2011)
This paper reports the results of the measurement of the viscosity of R134a close to the saturation line in the vapor phase. The new measurements were carried out in a vibrating-wire viscometer specially constructed for the purpose, and the results have an accuracy of ±2%. In addition, the opportunity is taken to present a reevaluation of earlier measurements along the saturation line of the viscosity of R32 and R125. Improved equations of state for these fluids are now available and can be employed to generate improved values for the viscosity.